Annexin V binding assay as a basophil activation test in an allergy to Secale cereale - Skotny, Anna; Gomułka, Krzysztof; Wolańczyk-Mędrala, Anna; Mędrala, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Diagnosis of allergic diseases is a problem that still cannot be easily overcome. An increasing number of studies have investigated achievement of flow cytometry as a very promising and helpful technique as an allergy diagnostic item. Different types of cells’ identification or activation markers and many research protocols have been shown. However there were no reliable trials that could allow to base the clinical decision on those proposed improvements. Annexin V is a cellular protein that is well known as a marker of early apoptosis but only a few papers mention its possible potential for being a marker of basophil activation [1, 2].